Migration Law and Influence of Proppant in Segmented Multicluster Fracturing Wellbore of Deep Shale Horizontal Well - Tingxue Jiang; Haitao Wang; Juanming Wei; Guanyu Zhong; Yucheng Zhao; Yushi Zou (Geofluids)
Intensive stage multicluster fracturing is the main technology of deep shale gas development, but this technology is easy to lead to the uneven propagation of multiple fractures. In order to deeply analyze the influence mechanism and law of proppant flow in the wellbore on multiple fractures and propagation, Firstly, based on the theoretical knowledge of computational fluid dynamics (CFD), a numerical model of solid-liquid two-phase flow of proppant migration in horizontal wellbore is established, which is calculated and solved by using the Euler-Euler multiphase-flow mixture model, and the effects of different influencing factors on the migration and distribution of proppant in wellbore are studied. Then, based on the fluid structure coupling theory, a planar three-dimensional (PL3D) numerical model of multicluster fracturing in horizontal wells is established. Taking the numerical simulation results of wellbore proppant migration as the initial condition, the influence law of proppant settlement on the fluid volume distribution among multiple clusters and the difference of multifracture geometry is clarified. The results show that the proppant content in the horizontal wellbore increases from heel end to toe end. The fracturing fluid viscosity and sand ratio are the main influencing parameters. The proppant settlement in the wellbore is also an important factor affecting the liquid and sand injection of multifracture. When considering the proppant settlement in the wellbore, the phenomenon of multifracture uneven propagation is more significant. The construction scheme of medium viscosity, large displacement fracturing fluid, large proppant size, and medium sand ratio in a certain range is conducive to promote the even propagation of multifracture. This study is helpful to guide the construction design of multicluster fracturing in horizontal wells, so as to improve the success rate of multicluster fracturing and greatly save the construction cost.